Pengenalan Konsep Kaizen 5-S Dan Karakter Sehat Sebagai Solusi Peningkatan Kompetensi Lulusan Memasuki Dunia Kerja Dan Industri Pada Siswa SMK Widya Praja Ungaran - Hendrike Priventa; Umi Handayani; Rosalina Wahyu Riani (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This service activity is carried out based on the problems that occur among vocational school graduates related to lack of competence and weak absorption in the world of work and industry. Based on the potential of Widya Praja Ungaran Vocational School as a partner, the Community Service program implementation team chose the hospitality department. The specific target is class XII students who must be prepared as prospective graduates who can be absorbed by industry. Also related to the team's field of knowledge, namely Japanese Literature and Education, the solution chosen was the concept of Kaizen 5-S and Healthy Character. The 5-S concept is a working principle of Japanese society that prioritizes self-management and the work environment. This concept was chosen because it is suitable for implementation with class XII vocational school students because it is easy to apply. Healthy character is one of the special characteristics of the vision of the Bachelor of Japanese Literature study program which can be published so that it is not only able to compete in field competencies but also has a person with healthy character in four (4) dimensions, namely ethics, literacy, aesthetics and kinesthetics. Therefore, the team proposed a community service program with the title "Introduction of the Relationship between the Kanzen 5-S Concept and Healthy Character in Students as Preparation for Entering the World of Work and Industry at Widya Praja Ungaran Vocational School." The method used is a socialization method using presentation media, flashcards, posters and booklets.